Quantifying structure and dynamics of bound and bulk polymer in tailor-made rubber-silica nanocomposites - Philippe, A.-M.; Sill, C.; Westermann, S.; Allgaier, J.; Staropoli, M.; Monkenbusch, M.; Gerstner, D.; Fleming, Y.; Wischnewski, A.; Hoffmann, I.; Zolnierczuk, P.; Do, C.; et al. (Frontiers in Physics, 2022)
The dynamics of long polymer chains in the presence of nanoparticles have been investigated. The nanocomposites were inspired by tire industry-like rubber materials and were made of entangled polyisoprene linear chains filled with chemically treated silica nanoparticles. Combining rheology, dielectric spectroscopy, and neutron spin echo measurements, we measured the modification of the polymer chain dynamics from bulk state to high filler concentration over a broad range of time and length scales. We show that the end-to-end relaxation does not seem to be impacted, whereas the polymer dynamics is significantly slowed down at a very local scale in presence of nano-fillers. Despite these different dynamics close and distant to the filler surface in the simple composites, additional Neutron Spin Echo spectroscopy experiment on labelled polymer chains, irreversibly bound to the filler surface and re-dispersed in a fully deuterated matrix, revealed a negligible dynamical behavior of this particular population of localized chains in the rubber layer. The conformational statistics of these chains is conformed to self-avoiding random walk trains within a shell that is thinner than the size of the chain. This work is the first of its kind which determines both the structure and the dynamic properties of chemically bound chains.